MicroRNA‐29b regulates DNA methylation by targeting Dnmt3a/3b and Tet1/2/3 in porcine early embryo development. (May 2018) - Zhang, Zhiren; Cao, Yunqing; Zhai, Yanhui; Ma, Xiaoling; An, Xinglan; Zhang, Sheng; Li, Ziyi
Abstract : MicroRNA‐29b (miR‐29b) is a member of the miR‐29 family, which targets DNA methyltransferases (DNMTs) and ten eleven translocation enzymes (TETs), thereby regulating DNA methylation. However, the role of miR‐29b in porcine early embryo development has not been reported. In this study, we examined the effects of miR‐29b in porcine in vitro fertilization (IVF) embryos to investigate the mechanism by which miR‐29b regulated DNA methylation. The interference of miR‐29b by its special miRNA inhibitor significantly up‐regulated Dnmt3a/b and Tet1 but downregulated Tet2/3 ; meanwhile it increased DNA methylation levels of the global genome and Nanog promoter region but decreased global DNA demethylation levels. The inhibition of miR‐29b also resulted in a decrease in the development rate and quality of blastocysts. In addition, the pluripotency genes Nanog and Sox2 were significantly downregulated, and the apoptosis genes Bax and Casp3 were upregulated, but anti‐apoptosis gene Bcl‐2 was downregulated in blastocysts. Our study indicated that miR‐29b could regulate DNA methylation mediated by miR29b‐ Dnmt3a/b – Tet1/2/3 signaling during porcine early embryo development. Abstract : Our study indicates that miR‐29b plays an indispensable role in regulating DNA methylation during porcine early embryo development mediated by miR29b‐Dnmt3a/3b ‐Tet1/2/3 signaling.